Reflections on the K-12 years in public schools: Relations with hearing teachers and peers from the perspective of deaf and hard-of-hearing adults - Joan M. Ostrove; Gina A. Oliva; Abigail Katowitz (Disability Studies Quarterly, 2009)
This study explores how members of systematically disadvantaged groups describe their interactions with members of dominant groups. In an effort to examine both positive and negative intergroup relations, this paper reports on a study of deaf and hard-of-hearing adults’ retrospective accounts of their best and worst experiences with hearing teachers and peers when they attended their local public schools during their K-12 years (Oliva, 2004). Written accounts from 60 deaf and hard-of-hearing adults were content analyzed. Their most positive experiences occurred when hearing teachers and peers were accommodating, encouraging, supportive, and interested in deafness. Negative reflections described hearing teachers and peers who were discriminatory, non-accommodating, and insensitive.